Impedance-Transforming Transdirectional Coupled-Line Directional Couplers With Maximum Achievable Transformation Ratio - Krzysztof Wincza; Kamil Staszek; Robert Smolarz; Slawomir Gruszczynski (IEEE Access)
A novel concept of impedance-transforming transdirectional coupled-line directional couplers that feature maximum available impedance transformation ratio is proposed. It is shown that such couplers can be designed as an appropriate connection of two uncoupled two-wire transmission lines, having electrical lengths equal 90° and 270°. The conditions for ideal impedance match and isolation in such couplers are derived and formulas describing the required characteristic impedances of the two two-wire transmission lines are given. It is shown that in such circuits the input and isolated port can be terminated with different impedances than the coupled and through ports. The major advantage of the proposed circuits is their reciprocity which allows for application in multiport amplifiers. The concept has been verified by the design and measurement of a 3-dB transdirectional coupler operating at a center frequency of 1 GHz that allows for achieving impedance transformation ratio $R =2$ proving the correctness of the presented analysis.